Moderating Effects of Authentic Happiness on the Relationship Between Health-seeking Behaviour and Treatment Adherence Among Patients with Hypertension - Fasanu O; Oderinde KO; Mustapha A (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
Background: Hypertension is a chronic health condition that requires consistent management and adherence to treatment. However, there is a dearth of empirical data on the psychological factors influencing treatment adherence among patients with hypertension in Nigeria. Objectives: To determine the moderating effects of authentic happiness on the relationship between health-seeking behaviour and treatment adherence among patients with hypertension. Methods: The study used a cross-sectional study design. Survey tools comprising items of the Authentic Happiness Scale, Health-seeking Behaviour Scale, Hill-bone Compliance High Blood Pressure Therapy Scale were used to obtain data from two hundred and ninety (290) patients who were selected by purposive sampling and met the study eligibility criteria. Results: Increase in health-seeking behaviour and authentic happiness showed significant effects on adherence to treatment [β1 = 0.241, t = 2.92, p = 0.004; β2 = 0.208, t = 4.80, p = 0.01 respectively]. The interaction between health-seeking behaviour and authentic happiness lacked significant effects on treatment adherence [β3 = 0.003, t = 0.032, p = 0.751]. The analysis of conditional effects revealed that the effects of health seeking behaviour on treatment adherence were significantly differentiated when happiness was low [β = 0.263, t = 2.46, p = 0.015], moderate [β = 0.241, t = 2.92, p = 0.004], or high [β = 0.219, t = 2.02, p = 0.044]. Conclusion: Health-seeking behaviour and authentic happiness are potential explanatory factors for adherence to treatment among patients with hypertension.